Prospek Pembelajaran Bahasa Arab di Era Generative Artificial Intelligence - Simon, Anis Shalatin (Pasca Sarjana IAIN Sultan Amai Gorontalo, 2023)
This research explores the role of Artificial Intelligence (AI), specifically Generative AI, in Arabic language learning and the importance of AI literacy for educators, students, and parents. Employing a qualitative method through a literature review, the study examines the extent of AI utilization in foreign language education, the prospects of Generative AI in Arabic language instruction, as well as the impacts and necessity of AI literacy. The findings indicate that Generative AI, such as ChatGPT, holds significant potential in enhancing Arabic language instruction. This AI can create tailored learning experiences, deliver interactive learning materials, and facilitate communication with native speakers. However, AI usage poses challenges, including issues of bias in generated outcomes. Hence, AI literacy is crucial for understanding the limitations and ethical use of this technology. The research underscores the need for the development of AI optimized for Arabic language education, while emphasizing the importance of ethical understanding and AI literacy for all stakeholders involved in education.